Boron bridging of rhamnogalacturonan‐II is promoted in vitro by cationic chaperones, including polyhistidine and wall glycoproteins - Chormova, Dimitra (New Phytol, 2016)
Dimerization of rhamnogalacturonan‐II (RG‐II) via boron cross‐links contributes to the assembly and biophysical properties of the cell wall. Pure RG‐II is efficiently dimerized by boric acid (B(OH)(3)) in vitro only if nonbiological agents for example Pb(2+) are added. By contrast, newly synthesized RG‐II domains dimerize very rapidly in vivo. We investigated biological agents that might enable this. We tested for three such agents: novel enzymes, borate‐transferring ligands and cationic ‘chaperones’ that facilitate the close approach of two polyanionic RG‐II molecules. Dimerization was monitored electrophoretically. Parsley shoot cell‐wall enzymes did not affect RG‐II dimerization in vitro. Borate‐binding ligands (apiose, dehydroascorbic acid, alditols) and small organic cations (including polyamines) also lacked consistent effects. Polylysine bound permanently to RG‐II, precluding electrophoretic analysis. However, another polycation, polyhistidine, strongly promoted RG‐II dimerization by B(OH)(3) without irreversible polyhistidine–RG‐II complexation. Likewise, partially purified spinach extensins (histidine/lysine‐rich cationic glycoproteins), strongly promoted RG‐II dimerization by B(OH)(3) in vitro. Thus certain polycations, including polyhistidine and wall glycoproteins, can chaperone RG‐II, manoeuvring this polyanionic polysaccharide domain such that boron‐bridging is favoured. These chaperones dissociate from RG‐II after facilitating its dimerization, indicating that they act catalytically rather than stoichiometrically. We propose a natural role for extensin–RG‐II interaction in steering cell‐wall assembly.